Phosphorylation and Ubiquitylation Regulate Protein Trafficking, Signaling, and the Biogenesis of Primary Cilia - May, Elena A.; Sroka, Tommy J.; Mick, David U. (Frontiers in Cell and Developmental Biology, 2021)
The primary cilium is a solitary, microtubule-based membrane protrusion extending from the surface of quiescent cells that senses the cellular environment and triggers specific cellular responses. The functions of primary cilia not only require numerous different components but also their regulated interplay. The cilium performs highly dynamic processes, such as cell cycle-dependent assembly and disassembly as well as delivery, modification and removal of signaling components to perceive and process external signals. On a molecular level, these processes often rely on a stringent control of key modulatory proteins, of which the activity, localization and stability are regulated by post-translational modifications. While an increasing number of post-translational modifications on ciliary components are being revealed, our knowledge on the identity of the modifying enzymes and their modulation is still limited. Here, we highlight recent findings on cilia-specific phosphorylation and ubiquitylation events. Shedding new light onto the molecular mechanisms that regulate the sensitive equilibrium required to maintain and remodel primary cilia functions, we discuss their implications for cilia biogenesis, protein trafficking and cilia signaling processes.